THE EFFECT OF FICTION MOVIE IN IMPROVING STUDENTS’ VOCABULARY - Rosmita Ambarita; Vera Kristiana; Ratna Sari Dewi (PHILOLOGY Journal of English Language and Literature, 2023)
The objective of the study was to investigate The Improving Students’ Vocabulary By Using fiction Movie. The population of the study was the second year of the students of STIE Alwashliyah Sibolga in 2021/2022 academic year, the total number of students was 80 students. The sample consist of two classes, there were 40 students of II A as an control group and II B as a experimental group. The method of the study was quantitative research with pre-experimental approach. The instrument used in this researcher was a vocabulary. The pre-test and post-test were administrated. Based on the calculation, the mean score of pre-test was 76.75 and mean of post-test was 9575. So, it could be stated that the hypothesis “Improving Students’ Vocabulary By Using Fiction Movie. Based on the result, it could be concluded that there was an improvement of the English vocabulary students through fiction Movie.